A Política Accountability e SPAECE: uma avaliação da performatividade na prática dos gestores escolares do Município de Aquiraz - Bastos, Érika Loiola (2025)
In Brazil, the Basic Education Assessment System (SAEB) consistsofpublic policies for large scale, nationwide external assessments that assess skills in the areas of Portuguese and Mathematics, and are applied in the final yearsofeachcycle (2nd, 5th and 9th grade of Elementary School and 3rd year of High School). Through SAEB, the National Institute of Studies and Educational Research Anísio Teixeira (INEP) performs a diagnosis of Basic Education and factors that may interfere with student performance. Influenced by the emergence of this external assessment policy, Ceará created the Permanent Basic Education Assessment System of Ceará (SPAECE), thus enabling the performance of its own assessment of its education network. As a result, manyactions are carried out within educational institutions with the aim of improving their educational indices. In this scenario, we seek answers to the following guiding question: What management practices are developed in theschoolcontext, in thesearch for betterresults in the SPAECE indicators, andthat lead to a cultureof performance? Guided by this question, this research has the general objective of: Evaluating the school management practices developed based on the results of SPAECE, as an accountability policy, with an emphasis on promoting performativity. In terms of public policy, the work is essentially based on the studies of Ball, Maguire and Braun (2016), Ball and Mainardes (2011) and Andrade (2023). The methodology used is of a basic nature, being characterized as exploratory and qualitative. As for the procedures, elements of bibliographic, documentary and field research were adopted. The research was carried out with a sample of three school managers from the municipal network of Aquiraz, Ceará, through semi-structured interviews and unsystematic observations of the school routine. The research the refore proceeded with a more critical and reflective analysis of the implications of SPAECE, as a public policy, in the school environment, especially with regard to the culture of performance. Among the findings of the research, the adoption of these preparatory practices for external evaluations stands out, resulting from a culture of performance that is fostered in the schools investigated, encouraging the subjects involved in the educational process to direct their actions towards meeting the objectives of public evaluation policies, thus reproducing characteristics of an accountability policy.